Handbook of air pollution prevention and control - Rao, Shrinivash (SCITUS Academics LLC, 2016)
Air Pollution Prevention and Control provides a concise overview of the latest technologies for managing industrial air pollution in petrochemical, oil and gas, and allied industries. Detailed material on equipment selection, sizing, and troubleshooting operations is provided along with practical design methodology. Unique to this volume are discussions and information on energy-efficient technologies and approaches to implementing environmental cost accounting measures. Uniquely combines prevention and control concepts while covering the practices and technologies that are applied to the prevention of air pollution in the chemicals manufacturing, oil and gas, iron and steel, and pharmaceutical industries, and to the cleaning and control of industrial air emissions. the reader should gain an appreciation for the simplicity of applying pollution prevention as opposed to incorporating engineering controls in many situations.